Green Jatropha Motor Oil (G-Jamo) synthesis using Treated Cockel Shell Waste (TCSW) catalyst - Said, N.; F. H., Ahmad; Jolius, Gimbun; N., Ibrahim; Mior Ahmad Khushairi, Mohd Zahari; Fatimah A., Misebah (2018)
Non-victual oil as inexhaustible reserves has risen an enthusiastic task for motor oil synthesis. Green synthesis of motor oil was run in a bath stirrer flask via two-stages catalytic transesterification. Reactions transesterification of trimethylolpropane (TMP) and Jatropha oil methyl ester (JOME) were carried out under treated cockle shell waste (TCSW) catalysts. Reaction time, catalyst loading, JOME and TMP ratio and temperature influence on G-JAMO (TMP-ester) were also investigated. The favourable triester composition (73.03%) and G-JAMO (TMP-ester) conversion (96.95%) were obtained by the JOME and TMP ratio of 1:4, time of 3 h, temperature of 110°C and catalyst loading of 3 wt/wt%. Synthesized lubricant oil performance gave viscosity index of 83, flash point of 215°C, density of 832 kg/m3, pour point of -6°C and kinematic viscosity at 40°C of 34.32 mm2/s. The physical chemical properties of Jatropha motor oil are appropriate with another plant oil feedstocks, used catalysts and justified standards. Utilization of non-edible and renewable corps, like Jatropha is expected to minimize issues of food supply chain.